The source of dietary non‐protein energy affects in vivo protein digestion in African catfish (Clarias gariepinus). (4th August 2014) - Harter, T.S.; Heinsbroek, L.T.N.; Schrama, J.W.
Abstract The development of chyme characteristics and the in vivo digestion of crude protein (CP) were assessed in response to different dietary sources of non‐protein energy. African catfish (Clarias gariepinus) were fed a starch or fat diet for 28 days, and faecal CP apparent digestibility coefficient (ADC) was determined by a marker method. After the consumption of a single meal, chyme was collected from four compartments of the gastrointestinal tract and viscosity, dry matter (DM), CP and marker concentration were measured. Replacing dietary fat by starch resulted in a lower faecal CP ADC (P < 0.05), even though CP originated from the same dietary ingredients. A higher inclusion level of starch led to a higher viscosity of chyme in the stomach, but a lower DM content, compared to the fat diet (P < 0.05). Gastric evacuation was delayed in starch fed fish, likely due to the high viscosity of chyme. After evacuation of chyme into the proximal intestine, no significant differences in chyme characteristics were observed between diets (P > 0.05). Changes in macronutrient composition can alter the environment in which CP digestion takes place. We suggest that for the formulation of highly digestible diets, the entire feed matrix needs to be considered, rather than single ingredients.